Risk Assessment for the Development of Metabolic Syndrome in Patients with AIDS After the First Year of Antiretroviral Therapy - Pejković, Miloš N; Stojić, Vladislava; Popovska-Jovičić, Biljana (Medicinski podmladak, 2019)
Introduction: Antiretroviral therapy (ART) in the treatment of HIV infection has allowed maximum control of viral replication and reconstruction of the immune system, which has contributed to the long-term survival. However, it has been observed that a long-term use of ART can lead to cumulative toxicity and metabolic abnormalities.Aim: The aim of this study was to determine whether there is a difference in lipidogram, glycemia and body mass index (BMI) before and after the initiation of ART, and to determine in which of the antiretroviral drugs the changes in the values of the measured variables were most common.Material and methods: The research was conducted at the Clinic for Infectious Diseases, Clinical Center of Kragujevac, as a prospective study involving 40 patients diagnosed with HIV infection. Biochemical parameters and BMI calculation were performed before the initiation of ART and one year after.Results: The analysis of the observed variables indicated a statistically significant difference in total cholesterol (p = 0.001), HDL (p = 0.002), LDL (p = 0.003), triglycerides (p < 0.001), glucose (p < 0.001) and BMI (p = 0.002). By analyzing the administered АRT therapy, statistical significance was achieved in the measured triglyceride values after the administration of ritonavir and lopinavir, while the highest BMI values, compared to initial ones, were observed after the administration of ritonavir, but without achieving statistical significance.Conclusion: The results of the study showed that АRТ therapy has effect on the development of hyperlipidemia, which may be associated with an increased risk of developing cardiovascular disease and protease inhibitors of the older generation are highlighted, in particular. АRT therapy in HIV-infected cells contributes to the development of a metabolic syndrome involving dyslipidemia, lipodystrophy and insulin resistance.Keywords: HIV, antiretroviral therapy, cardiovascular disease, protease inhibitors, hyperlipidemia